Experimental evaluation methods of multi-frequency electromagnetic radiation effects - Xiao-Peng Li; Guang-Hui Wei; Hong-Ze Zhao; Jiang-Ning Sun; Xu-Xu Lyu (AIP Advances)
Objective evaluation of equipment immunity to electromagnetic interference is central to studying complex electromagnetic environmental effects. Traditional single-frequency electromagnetic radiation immunity tests struggle to accurately assess the true anti-interference capabilities of the EUT in complex multi-frequency electromagnetic environments. Consequently, there is an urgent need to establish a multi-frequency electromagnetic radiation effect experimental evaluation method and testing process that accurately reflect the effect features. This study categorizes the research process of multi-frequency electromagnetic radiation effects on electronic equipment into three stages: pre-experiment, analysis-modeling, and model verification. The specific implications and research progress of the “mechanism analysis & effect testing” evaluation method are discussed from seven perspectives: observing susceptible phenomena, selecting susceptibility criterion, determining susceptible frequency bands, summarizing effect feature, analyzing effect mechanism, establishing evaluation model, and conducting model verification experiments. This framework provides essential technical support for research on multi-frequency electromagnetic radiation effects in electronic equipment.